2022
DOI: 10.14719/pst.1605
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting endophytic bacteria associated with Halocnemum strobilaceum (Pall.) M.Bieb and their plant beneficial traits

Abstract: Halocnemum strobilaceum (Pall.) M.Bieb. is a halophyte desert plant. The plant is known for its antioxidant, antimicrobial, insecticidal and phytoremediation properties. Halocnemum strobilaceum grows in severe salinity and drought conditions and its’ survival can be associated with activity of endophytic bacteria. The aim of the research was to reveal and study plant growth-promoting endophytic bacteria isolated from Halocnemum strobilaceum (Pall.) M.Bieb. The plants were collected from Kyzylkum desert in Uzbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…When plants grow in severe salinity and drought environments, the presence of endophytic bacteria in these plants may help them to survive and grow in these conditions. Several studies have shown the beneficial effects of endophytic bacteria on their host plants, such as the Salicornia brachiate [ 21 ] plant, Cicer arietinum [ 22 ], Haloxylon ammodendron [ 23 ], Nypa fruticans [ 24 ], Salicornia bigelovii [ 25 ], Armoracia rusticana [ 26 ], Seidlitzia rosmarinus [ 27 ], Calendula officinalis [ 28 ], Halocnemum strobilaceum [ 29 ], Haloxylon aphyllum [ 30 ], Tetragonia tetragonioides [ 31 ], and other plants. In this study, we have isolated an endophytic bacterium from the salt marsh halophyte, Bolboschoenus planiculmis .…”
Section: Introductionmentioning
confidence: 99%
“…When plants grow in severe salinity and drought environments, the presence of endophytic bacteria in these plants may help them to survive and grow in these conditions. Several studies have shown the beneficial effects of endophytic bacteria on their host plants, such as the Salicornia brachiate [ 21 ] plant, Cicer arietinum [ 22 ], Haloxylon ammodendron [ 23 ], Nypa fruticans [ 24 ], Salicornia bigelovii [ 25 ], Armoracia rusticana [ 26 ], Seidlitzia rosmarinus [ 27 ], Calendula officinalis [ 28 ], Halocnemum strobilaceum [ 29 ], Haloxylon aphyllum [ 30 ], Tetragonia tetragonioides [ 31 ], and other plants. In this study, we have isolated an endophytic bacterium from the salt marsh halophyte, Bolboschoenus planiculmis .…”
Section: Introductionmentioning
confidence: 99%
“…Like almost all xerophytes and halophytes, sarsazan does not have developed leaves, is able to accumulate salts in its tissues, and tolerates extreme soil salinity. Therefore, H. strobilaceum is classified as a hyperhalophyte (14,15). Data from the IR spectrum analysis were used to study soil samples around the root system of H. strobilaceum, as well as soil around it at the site of the studied drying lake.…”
Section: Methodsmentioning
confidence: 99%
“…Кроме того, эти корни являются источником галотолерантных N 2 -фиксирующих бактерий с потенциалом стимулирования роста растений [31], некоторые из которых усиливают рост галофитов, а также негалофитных культур на засоленных почвах. Потенциальные преимущества биологических фиксаторов азота для галофитов и чувствительных к засолению культур, подчеркивают интерес к изучению галотолерантных PGPR и эндофитных бактерий, фиксирующих N 2 , в качестве потенциальных источников биоудобрений для засоленных почв [32].…”
Section: фиксация азотаunclassified